The Effects of Hemodialysis on Tear Osmolarity - Muhittin Taskapili; Kubra Serefoglu Cabuk; Rukiye Aydin; Kursat Atalay; Ahmet Kirgiz; Dede Sit; Hasan Kayabasi (Journal of Ophthalmology)
Aim. To determine the effects of hemodialysis (HD) on tear osmolarity and to define the blood biochemical tests correlating with tear osmolarity among patients with end stage renal disease (ESRD). Material-Method. Tear osmolarity of ESRD patients before and after the hemodialysis program was determined as well as the blood biochemical data including glucose, sodium, potassium, calcium, urea, and creatinine levels. Results. Totally 43 eyes of 43 patients (20 females and 23 males) with a mean age of 53.98±18.06 years were included in the study. Tear osmolarity of patients was statistically significantly decreased after hemodialysis (314.06±17.77 versus 301.88±15.22 mOsm/L, p=0.0001). In correlation analysis, pre-HD tear osmolarity was negatively correlated with pre-HD blood creatinine level (r=-0.366,  p=0.016). Post-HD tear osmolarity was statistically significantly correlated with the post-HD glucose levels (r=0.305  p=0.047). Tear osmolarity alteration by HD was negatively correlated with creatinine alteration, body weight alteration, and ultrafiltration (r=-0.426,  p=0.004; r=-0.365,  p=0.016; and r=-0.320, p=0.036, resp.). There was no correlation between tear osmolarity and Kt/V and URR values. Conclusion. HD effectively decreases tear osmolarity to normal values and corrects the volume and composition of the ocular fluid transiently. Tear osmolarity alteration induced by HD is correlated with body weight changes, creatinine alterations, and ultrafiltration.